OPTIMASI PROSES PENGAJUAN FREE PARKING KARYAWAN MELALUI SISTEM BERBASIS WEB - Pandu Sajiwa; Anita Ratnasari (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
The process of applying for employee free parking facilities at A Mall is still conducted manually, leading to delays in approval, data recording errors, and limitations in real-time status monitoring. This study aims to optimize the management of employee free parking applications through an integrated web-based information system. The system was developed using the Waterfall method with Unified Modeling Language (UML) for system modeling, implemented using PHP and MySQL, and tested using black box testing. The testing results indicate that the system is able to accelerate the application processing time from an average of 2 days to less than 1 day and reduce data recording errors by up to 85% through the automation of submission and validation processes. Therefore, the developed system is effective in improving administrative efficiency, data accuracy, and centralized monitoring of employee free parking applications.